فهارس المؤلفين فى العصر الإسلامى: دراسة تاريخية. - أحمد جابر حامد (المجلة الدولية لعلوم المكتبات والمعلومات)
The research aims to explore authors' bibliographies that were prepared in Arabic, in the Islamic era from the second century to the middle of the fourteenth AH and its different types, and to know its contents & methods of preparation. To achieve that the research used the historical method by searching in Islamic bibliographies, bibliographies of Islamic manuscripts, biographies, and books of Islamic history. This in addition to the analysis of a number of available authors’ bibliographies. The study found129 bibliographies divided by kind into: general bibliographies, specialized bibliographies, study guides or reading ranks for authors’ books, biobibliographies for authors, and translators’ bibliographies. In term of wording they divided into: prose, and versified bibliography, all of them sought to achieve bibliographic goals. The study did not find authors’ bibliographies in the 1st century AH, but they began to appear in the 2nd after the Arabs knew it from the Greeks, during the movement of translating books from other civilizations. Style of bibliographic description differed between books in the same bibliography, and also between different bibliographies. The bibliographic data was limited and few, in general it consisted of: title, extent, size, subject, notes (included: the field, book evaluation, category of readers/ study level, contents, incomplete books, and date of authorship). Authors’ biobibliographies were closer to biographical books than bibliographies; because of their greater interest in bibliographic data. The study recommended seeking scientific study of all heritage bibliographies and providing them with searchtools, and then publishing them to facilitate free access .